Medicinally Used Asarum Species: High-Resolution LC-MS Analysis of Aristolochic Acid Analogs and In vitro Toxicity Screening in HK-2 Cells - Michl, Johanna; Bello, Olusheyi; Kite, Geoffrey C.; Simmonds, Monique S. J.; Heinrich, Michael (Frontiers in Pharmacology, 2017)
Species of Asarum are used in traditional Chinese medicine and similar to members of the genus Aristolochia they contain aristolochic acid analogues (AAAs). These compounds are known for their nephrotoxic and carcinogenic effects. So far, the phytochemistry and nephrotoxicity of species of Asarum is not well studied. A high-resolution LC-MS-based metabolomic approach was used to study the phytochemical variation in medicinally used Asarum species. The cytotoxicity of the samples was assessed using human kidney (HK-2) cells. The majority of samples contained potentially nephrotoxic AAAs, including 9-methoxy aristolactam (AL) IV, AL I and AL IV. These compounds were present in methanol as well as water extracts. AAAs were detected in all parts of the plant. The majority of the extracts were not cytotoxic to HK-2 cells at the doses tested. However, other mechanisms relating to aristolochic acid nephropathy and cancer development, such as DNA adduct formation may occur. The results of this study provide a model for assessing lesser-known plant species for toxicity.